Heterochromatin protein 1β (HP1β) has distinct functions and distinct nuclear distribution in pluripotent versus differentiated cells - Mattout, Anna; Aaronson, Yair; Sailaja, Badi Sri; Raghu Ram, Edupuganti V.; Harikumar, Arigela; Mallm, Jan-Philipp; Sim, Kae Hwan; Nissim-Rafinia, Malka; Supper, Emmanuelle; Singh, Prim B.; Sze, Siu Kwan; Gasser, Susan M.; et al. (Genome biology, 2015)
Pluripotent embryonic stem cells (ESCs) have the unique ability to differentiate into every cell type and to self-renew. These characteristics correlate with a distinct nuclear architecture, epigenetic signatures enriched for active chromatin marks and hyperdynamic binding of structural chromatin proteins. Recently, several chromatin-related proteins have been shown to regulate ESC pluripotency and/or differentiation, yet the role of the major heterochromatin proteins in pluripotency is unknown.
Gesehen am 09.06.2020